Field Evaluation of the New Rapid NG-Test® SARS-CoV-2 Ag for Diagnosis of COVID-19 in the Emergency Department of an Academic Referral Hospital - Avgoulea, Kalliopi; Beredaki, Maria-Ioanna; Vourli, Sophia; Siopi, Maria; Siafakas, Nikolaos; Pournaras, Spyros (Frontiers in Public Health, 2022)
Background: As the COVID-19 pandemic resurges due to novel variants, point-of-care diagnostics are important for rapid and convenient detection of cases. Objectives: We evaluated the NG-test SARS CoV-2 Ag immunochromatographic assay for qualitative detection of SARS CoV-2 antigens in naso-pharyngeal (NP) and oro-pharyngeal (OP) samples of walking patients who presented in the Emergency Department (ED) of our hospital, compared with RT-PCR. Methods: Totally 263 adult patients who were symptomatic, contacts of confirmed cases or follow-up cases, were enrolled. One NP and one OP samples were screened by NG-test in the ED, according to manufacturer’s instructions; another NP sample was tested by RT-PCR in the central laboratory, using Certest Viasure SARS-CoV-2 (CerTest Biotec, Spain) on a Rotor-Gene Q thermal cycler (Qiagen). PCR Ct values ≥35 were considered negative. Results: Out of 263 patients, 134 (51%) were RT-PCR-positive; of these, 108 (80.6%) were positive by NP NG-test and 68 (50.7%) by OP NG-test. The detection sensitivity for high viral loads (Ct<25) was 100%/74.6%, for NP/OP, respectively. All 12 (100%) NP false-negative results collected from symptomatic, not follow-up cases were correlated with Ct ranges ≥25, while the respective figure for OP results was 30 (69.8%). All 129 (49%) RT-PCR-negative tested negative by NP and OP NG-test (specificity 100%, 95% CI 97.7-100%). Conclusions: NG-test SARS CoV-2 Ag showed very satisfactory performance as a point-of-care test for NP samples obtained from symptomatic patients with acute infection. Negative results should be confirmed by RT-PCR; patients’ medical picture and history should also be considered.